Confirmation of a Ring Structure in the Disk Around Mp Mus (Pds 66 with Alma Band 7 Observations - Perez-Marquez, S (EDP Sciences, 2025)
Context. Young stellar objects (YSOs) are surrounded by protoplanetary disks, which are the birthplace of young planets. Ring and gap structures are observed among evolved protoplanetary disks, often interpreted as a consequence of planet formation. Aims. The pre-Main Sequence (pre-MS) star MP Mus hosts one of the few known examples of protoplanetary disks within 100 pc. Previously, a disk ring structure, with a radius of 80-85 au, was detected in scattered light via near-infrared polarimetric imaging. This ring structure may be indicative of the disk clearing process. Although such ring structures were not seen in the ALMA Band 6 images, some features were detected at ∼50 au. Methods. In this paper, we analyzed new ALMA Band 7 observations of MP Mus in order to investigate the details of its disk substructures. Results. By subtracting the continuum profile generated from Band 7 data, we discovered a ring structure in the Band 7 dust continuum image at ∼50 au. We calculated the overall dust mass as 28.4 ± 2.8 M⊙ at 0.89 mm and 26.3 ± 2.6 M⊙ at 1.3 mm and the millimeter spectral index α0.89-1.3 mm ∼2.2 ± 0.3 between 0.89 mm and 1.3 mm. Moreover, we display the spatial distribution of the spectral index (αmm), estimating values ranging from 1.3 at the inner disk to 4.0 at a large radius. Additionally, we observed an extended gas disk up to ∼120 au, in contrast with a compact continuum millimeter extent of ∼60 au. Conclusions. We conclude that there are strong indicators for an active radial drift process within the disk. However, we cannot discard the possibility of a dust evolution process and a grain growth process as responsible for the outer disk structures observed in the ALMA continuum imaging. © The Authors 2025.